2022
DOI: 10.2166/wpt.2022.001
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of industrial electroplating wastewater for metals removal via electrocoagulation continous flow reactors

Abstract: A real industrial electroplating rinsing wastewater was collected and subjected the physical and chemical examination. The study showed that it can be categorized as high strength wastewater, at pH- 2, COD 1430 mg/l, and high level of metals above permissible limits namely: 150, 30, 25, and 2.9 for Ni, Cu, Zn, and Fe mg/l respectively. Therefore, metals must be adequately removed before discharging to avoid any hazardous impact on the environment. Similar synthetic wastewater was prepared to study effect of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…The findings demonstrated that the high removal efficiency (97.4% and 96.6% for zinc and copper, respectively) was obtained at pH 6 using a high amount of sludge (1.4 g) [ 58 ]. Other studies indicated that the application of an electrocoagulation process for high strength industrial electroplating wastewater (pH 2, COD 1 430 mg O 2 /L, Ni 150 mg/L, Cu 30 mg/L, Zn 25 mg/L and Fe 2.9 mg/L) made it possible to remove 92.1% Ni, 87.8% Zn and 82.9% Cu [ 59 ]. In the case of using agricultural wastes as adsorbents, the highest efficiency of zinc removal (63.6%) was obtained at pH 6 [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings demonstrated that the high removal efficiency (97.4% and 96.6% for zinc and copper, respectively) was obtained at pH 6 using a high amount of sludge (1.4 g) [ 58 ]. Other studies indicated that the application of an electrocoagulation process for high strength industrial electroplating wastewater (pH 2, COD 1 430 mg O 2 /L, Ni 150 mg/L, Cu 30 mg/L, Zn 25 mg/L and Fe 2.9 mg/L) made it possible to remove 92.1% Ni, 87.8% Zn and 82.9% Cu [ 59 ]. In the case of using agricultural wastes as adsorbents, the highest efficiency of zinc removal (63.6%) was obtained at pH 6 [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…It utilizes the principles of electrochemistry and flotation to separate and concentrate suspended particles, such as contaminants, solids, or oils, from water or wastewater. Nevertheless, a comprehensive comparison of these methods under consistent operational parameters and energy consumption has not been conducted, making it challenging to determine whether the “electrochemical ion pumping” method surpasses metal extraction techniques from natural saline sources [ 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 ].…”
Section: Discussionmentioning
confidence: 99%
“…Abdel-Shafy et al [41] diseñaron una secuencia experimental cuya finalidad radicó en aminorar la cantidad de Ni, Cu y Zn en aguas de industria de galvanoplastia. Las etapas sucesivas fueron coagulación, electrocoagulación, un proceso continuo para enlazar ambas destinado primero al agua sintética y enseguida al agua residual real.…”
Section: Electrocoagulación De Aguas Residualesunclassified